2020
DOI: 10.1371/journal.pone.0230043
|View full text |Cite|
|
Sign up to set email alerts
|

The gender gap in commenting: Women are less likely than men to comment on (men’s) published research

Abstract: Subtle gender dynamics in the publishing process involving collaboration, peer-review, readership, citation, and media coverage disadvantage women in academia. In this study we consider whether commenting on published work is also gendered. Using all the comments published over a 16-year period in PNAS (N = 869) and Science (N = 481), we find that there is a gender gap in the authorship of comment letters: women are less likely than men to comment on published academic research. This disparity is greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…For example, it is also possible that men might volunteer more readily to take up this time-consuming role -our data does not allow us to shed any light on the inner discussions beyond response time. Regardless, our effect is consistent with other studies showing that women are disproportionately engaged in internalinstitutional facing duties, whereas men are disproportionately engaged in community-facing roles, which are also more associated with eminence, networking, and other benefits related to the more visible duties of the reviewing RE leading the peer review (11,13,19,21,67). The reasons underlying this pattern should be further studied, however women's different time allocation may reflect a purposeful choice to contribute to their institutions.…”
Section: Gender Disparitiessupporting
confidence: 89%
See 1 more Smart Citation
“…For example, it is also possible that men might volunteer more readily to take up this time-consuming role -our data does not allow us to shed any light on the inner discussions beyond response time. Regardless, our effect is consistent with other studies showing that women are disproportionately engaged in internalinstitutional facing duties, whereas men are disproportionately engaged in community-facing roles, which are also more associated with eminence, networking, and other benefits related to the more visible duties of the reviewing RE leading the peer review (11,13,19,21,67). The reasons underlying this pattern should be further studied, however women's different time allocation may reflect a purposeful choice to contribute to their institutions.…”
Section: Gender Disparitiessupporting
confidence: 89%
“…This gender gap in representation and career advancement is present across all career stages (1,(6)(7)(8)(9). For example, beyond the clear disproportionate representation of men over women in senior investigator categories, women receive fewer and less prestigious awards (10)(11)(12)(13)(14), obtain fewer grants (15)(16)(17), are less frequently invited to write review or comment papers (18)(19)(20)(21), and have lower salaries relative to men (6,7,22). Gender disparities at senior levels are also noticeable for services to the broader scholarly community, where men are more likely to provide higher status external service, whereas women tend to perform lower status internal service (11,23).…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing the gender pairs of first and last author, an overall pattern of gender homophily was apparent as evidenced in previous studies in STEMM fields [ 23 , 31 , 32 ]. A study by Holman et al [ 31 ] found that researchers tend to work with same gendered colleagues across disciplines in the life sciences, which included dentistry.…”
Section: Discussionsupporting
confidence: 57%
“…It has been suggested that women have a lower wage [7,8], are promoted more slowly [9], receive less research funding [10], and their proportion in editorial and faculties boards is lower [2] A different line of studies of gender imbalance has focused on knowledge production. There is a wide choice of literature discussing the persistence of gender differences in the production and publication of scientific knowledge, such as bias in the journal reviewing process [11], differences in the number of citations of their work in comparison with their male colleagues [11], a gender asymmetry in collaborations [12] or even, a disparity in commenting on published academic research [13].…”
mentioning
confidence: 99%